2004
DOI: 10.1089/104454704774076190
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Dentine Permeability after Apicectomy and Surface Treatment with 9.6 µm TEA CO2and Er:YAG Laser Irradiation

Abstract: Failure of apicectomies is generally attributed to dentine surface permeability as well as to the lack of an adequate marginal sealing of the retrofilling material, which allows the percolation of microorganisms and their products from the root canal system to the periodontal region, thus compromising periapical healing. The purpose of this study was to evaluate dentine and the marginal permeability after apicectomy and surface treatment with 9.6 micro m TEA CO(2) or Er:YAG 2.94 micro m laser irradiation. Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 44 publications
0
26
0
3
Order By: Relevance
“…Surfaces cut with burs were the smoothest and so exhibited the greatest dentin permeability, followed by those cut with the Er:YAG and CO 2 lasers. The latter resulted in the least dentin permeability as a result of the melting and recrystallization of the dentin, obliterating dentin tubules (9). With relation to the presence of failures at the interface between the dentin and the obturation material, the bur group had the lowest incidence and the smallest size failures, resulting in flatter surfaces and less gutta-percha displacement when compared with the other groups.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Surfaces cut with burs were the smoothest and so exhibited the greatest dentin permeability, followed by those cut with the Er:YAG and CO 2 lasers. The latter resulted in the least dentin permeability as a result of the melting and recrystallization of the dentin, obliterating dentin tubules (9). With relation to the presence of failures at the interface between the dentin and the obturation material, the bur group had the lowest incidence and the smallest size failures, resulting in flatter surfaces and less gutta-percha displacement when compared with the other groups.…”
Section: Discussionmentioning
confidence: 94%
“…Root surfaces irradiated with CO 2 laser have craters presenting a carbonized superficial layer, forming a matrix similar to cementum and absence of dentin tubules (8). In addition, human teeth apicectomized using Er:YAG laser and CO 2 laser compared to burs had smoother surfaces and more homogeneous fusion and recrystallization, with occluded tubules and reduced permeability (9). The objective of this study was to investigate apicectomies performed using burs or laser technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 9.6micrometer CO2 laser wavelength is highly absorbed in appetite crystals, it presents a future potential for its applications in cavity preparation, apicectomies and other hard tissue procedures. In vitro study using Scanning Electron Microscopic (SEM) images reported cleaner dentinal surface with fusion and recrystallized dentine following apicectomy and root treatment with pulsed TEA 9.6micrometer CO2 laser (Gouw-Soares et al, 2004). Contrasting results were reported in a more recent SEM analysis study.…”
Section: Endodontics (Apicoectomy Root Canal Debridement)mentioning
confidence: 81%
“…For example, Nd:YAG and Diode lasers are absorbed by dark pigments making them ideal for soft tissue procedures. Tissue component that maximally absorbs CO2 wavelength is water followed by apatite (Gouw-Soares et al, 2004). Because of this CO2 lasers have been proven to be the gold standard for intra-oral soft tissue applications for decades.…”
Section: Basic Equipment Design and Tissue Interactions Of Co2 Lasermentioning
confidence: 99%
“…In an attempt to increase the successful rate of endodontic surgical procedures, Gouw-Soares et al 18 showed that…”
Section: Effect On Treatment Outcomementioning
confidence: 99%